An improved ileal conduit surgery for bladder cancer with fewer complications. Issue 1 (18th April 2019) - Li, Zhiyong; Liu, Zhuowei; Yao, Kai; Qin, Zike; Han, Hui; Li, Yonghong; Dong, Pei; Ye, Yunlin; Wang, Yanjun; Wu, Zhiming; Zhang, Zhiling; Zhou, Fangjian
Abstract: Background: Radical cystectomy and urinary diversion remains the standard surgical treatment for patients with muscle‐invasive or high‐risk or recurrent non‐muscle‐invasive bladder cancer. Although this approach prolongs patient survival remarkably, there are postoperative complications associated with urinary diversion. This study aimed to assess the efficacy of modified ileal conduit surgery for reducing early and late stoma‐ and ureteroileal anastomosis‐related complications, as compared with conventional ileal conduit urinary diversion. Methods: We retrospectively evaluated the clinical data of bladder cancer patients treated with radical cystectomy and ileal conduit urinary diversion at Sun Yat‐sen University Cancer Center between January 1, 2000 and June 30, 2016. Ileal conduit was created by the conventional or a modified technique. The clinicopathologic features of the conventional and the modified ileal conduit groups were compared using the t test and the Chi square test. Multivariable logistic regression analysis and multivariable Cox regression analysis were performed to determine the odds of developing stoma‐ and ureteroileal anastomosis‐related complications in the two groups. Results: 145 and 100 patients underwent the modified and conventional ileal conduit surgery, respectively. The two groups were comparable with regard to clinicopathologic features. The rate of stoma‐related complications was significantly lower in the modified ileal conduit group than in the conventional ileal conduit group (0.7% vs. 17.0%, P < 0.001). No late stoma‐related complications were seen in the modified ileal conduit group, but were seen in 13 (13.0%) patients in the conventional ileal conduit group. The rate of ureteroileal anastomosis‐related complications was significantly lower in the modified ileal conduit group than in the conventional ileal conduit group (4.8% vs. 15.0%, P = 0.001). In multivariable analyses, the modified ileal conduit group was significantly less likely to develop stoma‐ (odds ratio [OR] = 0.024, 95% confidence interval [CI] 0.003–0.235; P = 0.001) or ureteroileal anastomosis‐related complications (OR = 0.141, 95% CI 0.042–0.476; P = 0.002) than the conventional ileal conduit group. Conclusions: Our modified surgical technique for ileal conduit urinary diversion may be effective for reducing early and late complications related to the stoma and the ureteroileal anastomosis. Prospective randomized clinical trials are needed to confirm our results.